Analysis Of Public Service Quality Using the SERVQUAL Model At The Majalengka Regency Department Of Population And Civil Registration - Muhamad Iman Abdurohman; Hery Nariyah (ann4publisher@gmail.com, 2026)
Background. The quality of population administration services is a critical determinant of public trust and effective governance, particularly in the issuance of birth and death certificates, which serve as essential legal documents. Despite improvements in Indonesia's public service performance, disparities in service quality remain evident at the local government level. Aims. This study aims to analyze the quality of birth and death certificate services at the Majalengka Regency Population and Civil Registration Office using the SERVQUAL framework. A qualitative descriptive approach was employed, with data collected through semi-structured interviews, direct observations, and document analysis. Informants included service officers, service users, and village- level administrative representatives. Data were analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing, while credibility was enhanced through source and method triangulation. Result. The findings indicate that service quality generally falls within the good to fairly good categories across the five SERVQUAL dimensions. Reliability and assurance emerged as the strongest dimensions, supported by standardized operating procedures, competent personnel, electronic verification, and digital signature systems that ensure service accuracy and legal certainty. In contrast, tangibles, responsiveness, and empathy remain constrained by limited physical facilities, high service demand, technical disruptions, and human resource capacity during peak service periods. Conclusion. The study demonstrates that institutionalized service systems contribute to more consistent service quality than dimensions that rely primarily on individual staff performance. Implication. These findings extend the application of SERVQUAL as a qualitative analytical framework in public administration and provide practical recommendations for strengthening infrastructure, human resource capacity, and interagency coordination to improve the consistency and sustainability of civil registration services.